A Study on the Influencing Factors of Students' Academic Performance in Guangdong Private University, China - Yu, Qiao (Scholar: Human Sciences, 2025)
Purpose: This study aims to examine the factors, which include school culture, teacher commitment, teacher emotional intelligence, teacher collective efficacy, and teacher instructional leadership, that improve students’ academic performance in a private university in Guangdong. Research design, data, and methodology: A group of 30 students attend a 16-week strategic plan. A cohort of 146 students participated in the action research, employing a mixed-method approach that combines qualitative and quantitative methods to examine the impact of the strategic plan. The Instrument of Item Objective Congruence (IOC) has undergone validation by three experts, and the scale’s reliability and validity meet research standards. Hypotheses regarding the correlation between the five variables—school culture, teacher commitment, teacher emotional intelligence, teacher collective efficacy, teacher instructional leadership—and students’ academic performance have been statistically confirmed with significance. Results: Research findings demonstrate significant changes in school culture, teacher commitment, teacher emotional intelligence, teacher collective efficacy, teacher instructional leadership, and student academic performance before and after the strategic plan. Conclusions: The results confirmed that the strategic plan designed in this study positively impacted college students’ academic performance levels. It was evident that school culture, teacher commitment, emotional intelligence, collective efficacy, instructional leadership, and students’ academic performance showed significant improvements after the strategic plan.